Penyuluhan Efek Penggunaan Smartphone Pada Anak Usia Dini - Wahyu Adi Prabowo; Amalia Beladinna Arifa; Yohani Setiya Rafika Nur (LPPM IT Telkom Purwokerto, 2023)
This community service activity aims to enhance the knowledge of parents and children regarding the use of smartphones in the teaching and learning process at Srambi Paud Center Purwokerto. The counseling sessions were conducted to assist parents in supervising their children's smartphone usage in their daily activities. The training took place in the auditorium of Srambi Paud Center Purwokerto and successfully improved the understanding of both parents and children regarding smartphone usage in general, as well as providing an understanding of the positive and negative effects that may arise from smartphone use. The participants also successfully applied the outcomes of the counseling sessions by seeking and utilizing more diverse and attention-grabbing learning media through smartphones. Additionally, this activity successfully enhanced the motivation of teachers to create engaging teaching materials by utilizing technology, thus facilitating the delivery of lessons to the children. During the counseling practice, participants were tasked with finding learning media through smartphones and creating teaching materials for subjects frequently taught by each teacher. The results of the practice showed that 95% of the teachers were able to create learning media for the children. Therefore, this activity succeeded in improving the knowledge of parents and children regarding smartphone usage and provided significant benefits for learning at Srambi Paud Center Purwokerto